Cooperación Documental : el caso de México. - Sagredo Fernández, Félix; Hernández Pacheco, Federico (Revista General de Información y Documentación, 2002)
This work introduces the cooperation channels developed by the documental bodies in México. It describes a general panorama in which are included, so as to give a clear idea as to relationships, the types of libraries, professional activities, librarianship training and research, the impact of technology, document cooperation and the information resources supporting the aforementioned channels.
Keywords: Cooperation; México; Documentation; Librarians; Congresses